2016
DOI: 10.1371/journal.pone.0153838
|View full text |Cite
|
Sign up to set email alerts
|

Depression as a Risk Factor for the Initial Presentation of Twelve Cardiac, Cerebrovascular, and Peripheral Arterial Diseases: Data Linkage Study of 1.9 Million Women and Men

Abstract: BackgroundDepression is associated with coronary heart disease and stroke, but associations with a range of pathologically diverse cardiovascular diseases are not well understood. We examine the risk of 12 cardiovascular diseases according to depression status (history or new onset).MethodsCohort study of 1,937,360 adult men and women, free from cardiovascular disease at baseline, using linked UK electronic health records between 1997 and 2010. The exposures were new-onset depression (a new GP diagnosis of dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
116
3
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 32 publications
5
116
3
12
Order By: Relevance
“…In the present study, the use of antidepressants in two consecutive years, indicating higher severe depression, was associated with short-term mortality from CHD. This finding is consistent with a prior study suggesting that adults with new onset of depression had higher risk of unheralded CHD death compared with non-depressed individuals 31. More severe and longer lasting depression may be related to the manifestation of more acute and proximate determinants or risk factors of CHD, such as diminished heart rate variability, which may be driving the association of much higher mortality for more severely depressed individuals with incident CHD.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the use of antidepressants in two consecutive years, indicating higher severe depression, was associated with short-term mortality from CHD. This finding is consistent with a prior study suggesting that adults with new onset of depression had higher risk of unheralded CHD death compared with non-depressed individuals 31. More severe and longer lasting depression may be related to the manifestation of more acute and proximate determinants or risk factors of CHD, such as diminished heart rate variability, which may be driving the association of much higher mortality for more severely depressed individuals with incident CHD.…”
Section: Discussionsupporting
confidence: 91%
“…Further, in peripheral artery disease, depressive symptoms are associated with increased cardiovascular mortality [60]. Depression and vascular disease are both common among the elderly, and cardiac dysfunction in association with depression is well documented [46, 61, 62]. These observations may provide clues about the mechanistic relationships, as depression-associated changes of peripheral vascular resistance are essential for the association of MDD with cardiovascular disease [63, 64].…”
Section: Resultsmentioning
confidence: 99%
“…It is acknowledged that old age depression is a heterogeneous illness with high treatment resistance associated with a number of contributing neurobiological factors, including CVD, neurodegeneration, inflammation, and others, all of which also contribute to its longitudinal prognosis and course [32, 166]. Elderly people are probably vulnerable to depression, and cardiovascular disease, diabetes mellitus, high cholesterol levels, and other such diseases increase the risk for LLD [32, 46, 61, 86, 224]. Drugs used for cardiovascular disease, such as beta blockers, may also potentially cause depression.…”
Section: Discussionmentioning
confidence: 99%
“…This was corroborated by a recent study from the University College London, which examined depression status as a risk factor for 12 cardiovascular diseases in almost 2 million men and women; it was shown that depression was prospectively associated with cardiac, cerebrovascular, and peripheral diseases, with no evidence of disease specificity [16]. Further research is therefore needed in understanding the specific pathophysiology of heart and vascular disease triggered by depression in healthy populations.…”
mentioning
confidence: 73%